Effect of dietary chitosan oligosaccharide complex with Ce (IV) on growth, immunity and disease resistance against Vibrio splendidus of sea cucumber, Apostichopus japonicas. (23rd February 2016) - Wang, Yanlong; Xu, Wei; Zuo, Rantao; Zhou, Huihui; Bai, Yang; Mai, Kangsen; Wang, Dongfeng; Ai, Qinghui
Abstract: An 8‐week feeding trial was conducted to investigate the effects of dietary chitosan oligosaccharide complex with cerium (Ce IV) (COS‐Ce) on growth performance, nonspecific immunity and disease resistance of sea cucumber, Apostichopus japonicas . Five isonitrogenous (18.6%) and isolipidic (1.1%) practical diets were formulated with graded level of COS‐Ce (0, 150, 300, 600 and 1200 mg kg −1 dry feed), which were named as COS‐Ce/0, COS‐Ce/150, COS‐Ce/300, COS‐Ce/600, COS‐Ce/1200 respectively. Each diet was allocated to four replicates of sea cucumbers (Initial weight: 6.72 ± 0.02 g). Sea cucumbers were fed to apparent satiation once daily (19:00 hours) for 56 days. During the experiment, water temperature was kept at 16 ± 0.5°C, pH 7.8–8.2, dissolved oxygen beyond 5 mg L −1, ammonia nitrogen below 0.5 mg L −1 and salinity from 30‰ to 31‰. Results showed that the specific growth rate of sea cucumbers was significantly higher in COS‐Ce/600 than that in other four treatments. Activities of phagocytosis, respiratory burst, acid phosphatase and alkaline phosphatase in COS‐Ce/600 were significantly higher than that in COS‐Ce/0 ( P  < 0.05) respectively. On the contrary, cumulative mortality was the lowest in COS‐Ce/600 following 14 days exposure to Vibrio splendidus ( P  < 0.05). In conclusion, these results confirmed that dietary COS‐Ce had beneficial effects on growth performance, nonspecific immunity and disease resistance of sea cucumber.